Contextual Effect of the Integrated Health Post and Other Determinants on Completeness of Basic Child Immunization: A Multilevel Analysis Evidence from Jember, East Java - Erynda, Revina Fiandany; Sulaeman, Endang Sutisna; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background: Every year, more than 1.4 million children worldwide die from diseases that can be prevented by immunization. Immunization is still one of the most cost-effective preventive mea